A superação do pensamento metafísico na filosofia política de Jürgen Habermas - Scaldaferro, Maikon Chaider Silva (2010)
The modern political theory tried to legitimate the democratic rule of law based on metaphysical principles. Thus, a crisis of metaphysical thinking leads to a crisis of legitimacy of the democratic rule of law. The deficit of legitimacy is enlarged for a lack of a religious unifier power, able to organize secular societies, and the absence of a common ethos, shared for secular citizens. It is in this historical context that Jürgen Habermas’ thinking emerges. This work aims to analyses the fundamentation of democratic rule of law in Jürgen Habermas’ philosophy. It states that Habermas overcomes the metaphysical thinking in your discourse theory. In the first chapter, we explain how Habermas comprehend the main features of the metaphysical thinking and the causes of metaphysic’s collapse. The second chapter demonstrates that the Frankfurt’s philosopher elaborates a theory of rationality and an ethics post-metaphysical. This post-metaphysical ethics is the point of departure for the development of habermasian political philosophy. At the third chapter, we examine how the democratic rule of law is reconstructed from a post-metaphysical base. Here the habermasian proposal is compared with the republicanism and the liberalism that present a metaphysical fundamentation of democratic state. Finally, as conclusion of our study, we debated the results of Habermas’ post-metaphysical political philosophy.